Comparision between body mass index and abdominal obesity for the screening for diabetes in healthy individuals - Gopinath, S. (Medknow Publications & Media Pvt Ltd, 2012)
AIM: To study about the usefulness of Waist-Height Ratio as a clinical marker in patients with Metabolic Syndrome. MATERIALS AND METHODS: A clinic-based study of patients attending a secondary level Diabetic Clinic and correlation of their Anthropometry data like waist circumference, height to other parameters namely body mass index (BMI), Waist-Hip Ratio, Blood pressure, Glycemic Control, Lipid Profile, and Duration of Diabetes. INCLUSION CRITERIA: Randomly selected 10 000 patients attending a secondary level diabetic clinic. EXCLUSION CRITERIA: Type 1 DM, Gestational Diabetes. RESULT: Waist-Height Ratio is a better parameter than Waist-Hip Ratio and it is significant in applying for people with different Stature with Normal BMI. CONCLUSION: Waist-Height Ratio is a better and easier tool when compared with BMI or Waist-Hip Ratio and can be used for assessment of Cardio-metabolic parameter for public health.